2017
DOI: 10.4014/jmb.1702.02069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Factors on Cyanobacterial Production of Odorous Compounds: Geosmin and 2-Methylisoborneol

Abstract: Geosmin and 2-methylisoborneol (2-MIB), responsible for earthy or musty smell, are a major concern for safe drinking water supplies. This study investigated the effects of environmental factors on odorous compound production and cell growth in cyanobacterial strains. sp. FACHB-1384, a 2-MIB producer, was sensitive to low temperature (<20°C). However, geosmin producers, sp. Chusori and sp. NIER, were sensitive to high light intensity (>100 μmol/m/sec), but not to low temperature. Geosmin concentrations increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…In Australia, Jones and Korth [52] showed that the production of geosmin by Anabaena sp. was 0.01 pg/cell, which was a very low concentration compared to the figure found by Li et al Oh et al [53] reported that Anabaena sp. produced extracellular geosmin at 1-2 pg/cell under different nitrogen concentrations.…”
Section: Algal-derived Taste and Odor Compoundscontrasting
confidence: 54%
See 3 more Smart Citations
“…In Australia, Jones and Korth [52] showed that the production of geosmin by Anabaena sp. was 0.01 pg/cell, which was a very low concentration compared to the figure found by Li et al Oh et al [53] reported that Anabaena sp. produced extracellular geosmin at 1-2 pg/cell under different nitrogen concentrations.…”
Section: Algal-derived Taste and Odor Compoundscontrasting
confidence: 54%
“…was 100-380 ng/µg Chl-a under variable temperature levels. Therefore, the parameter applied in this study was most similar to the values given in Jüttner and Watson [12] and Oh et al [53]. When taste and odor compounds as algal metabolites were modeled, the model accurately simulated the overall concentrations of 2-MIB ( Figure 6) and geosmin ( Figure 7).…”
Section: Algal-derived Taste and Odor Compoundsmentioning
confidence: 70%
See 2 more Smart Citations
“…Light intensity, photoperiod, and light quality have a big influence on the growth and metabolism of photosynthetic organisms including cyanobacteria. This is the reason why many studies exist about the influence of these parameters on cyanobacteria production of secondary metabolites and growth [25][26][27]. For instance, studies focusing on cyanobacterial growth show that Nostoc calcicola has 50% better growth under low light intensities than high intensities [25].…”
Section: Introductionmentioning
confidence: 99%